Small bowel ischaemia. (March 2015) - Varty, Kevin
Abstract Small bowel ischaemia can present acutely as an abdominal surgical emergency or as a more chronic condition, usually due to slow atherosclerotic occlusion of the visceral arteries. Early diagnosis of acute bowel ischaemia is essential. Other common causes of acute abdominal pain must be ruled out. CT scanning is the key investigation with an approximate 90% sensitivity and specificity. Plasma markers such as raised lactate can support the diagnosis but should not be relied upon. Due to the rapid deterioration that occurs with transmural necrosis, a low threshold for early surgical intervention with laparoscopy or laparotomy is needed. Non-viable bowel must be resected, and on-table revascularization may reduce the amount of bowel lost. Patients requiring extensive bowel resection will need subsequent home total parenteral nutrition and some can be considered for small bowel transplantation. Clot lysis can be beneficial for venous thrombosis. Chronic mesenteric ischaemia is commonly due to gradual atherosclerotic occlusion or stenosis of the mesenteric arteries (coeliac, superior mesenteric, inferior mesenteric). Presentation is with mesenteric angina, weight loss, and food fear. Widespread co-existent vascular disease, and smoking-related chronic obstructive pulmonary disease. Duplex sonography of the mesenteric vessels is not easy. CT or MR angiography are required to confirm the diagnosis and plan intervention. Angioplasty and stenting produce good short-term outcomes but re-stenosis is common and requires monitoring. Surgical endarterectomy or bypass give more durable results but with higher morbidity and mortality rates.